KEBIJAKAN PEMBENTUKAN KOMUNITAS ASEAN 2015: TANTANGAN DAN HARAPAN DALAM PENCIPTAAN STABILITAS KAWASAN - Hendra Maujana Saragih (Jurnal Administrative Reform, 2017)
This article aim to describe and analyze the challenges for Southeast Asia region in regards of ASEAN Community 2015 in order to create regional stability. The method used in this research is qualitative descriptive. The result shows that ASEAN security community focused only on cooperative security hence this community would never transformed into collective security and collective defenceKeyword : Regional Policy, ASEAN, Security